Melanocortin 4 receptor signaling in Sim1 neurons permits sexual receptivity in female mice - Semple, Erin A.; Harberson, Mitchell T.; Xu, Baijie; Rashleigh, Rebecca; Cartwright, Tori L.; Braun, Jessica J.; Custer, Amy C.; Liu, Chen; Hill, Jennifer W. (Frontiers in Endocrinology, 2023)
Female sexual dysfunction affects approximately 40% of women in the United States, yet few therapeutic options exist for these patients. The melanocortin system is a new treatment target for hypoactive sexual desire disorder (HSDD), but the neuronal pathways involved are unclear. In this study, female MC4R knockout mice lacking melanocortin 4 receptors (MC4Rs) were found to approach males less and have reduced receptivity to copulation, as indicated by a low lordosis quotient. These changes were independent of body weight. The mice were then bred to express MC4Rs exclusively on Sim1 neurons (tbMC4RSim1 mice) or on oxytocin neurons (tbMC4ROxt mice). Lordosis behavior was normalized in tbMC4RSim1 mice and improved in tbMC4ROxt mice. In contrast, approach behavior was unchanged in tbMC4RSim1 mice but greatly increased in tbMC4ROxt animals. The changes were independent of melanocortin-driven metabolic effects. These results implicate MC4R signaling in Oxt neurons in appetitive behaviors and MC4R signaling in Sim1 neurons in female sexual receptivity, while suggesting melanocortin-driven sexual function does not rely on metabolic neural circuits.